Case report: Artemis deficiency and 3M syndrome—coexistence of two distinct genetic disorders - Ceylan, Ayca; Tekdemir, Ilyas Emre; Kocak, Nadir; Chinn, Ivan Kingyue; Orange, Jordan Scott; Artac, Hasibe (Frontiers in Pediatrics, 2023)
The presence of two different genetic conditions in the same individual is possible, especially in populations with consanguineous marriage. In this case report, we present the coexistence of Artemis deficiency (OMIM 602450) and Three M (3M) syndrome (OMIM 273750). A 10-months-old male patient with neuromotor developmental delay was evaluated for immunodeficiency due to recurrent respiratory infections diarrhea and oral moniliasis from the age of 1.5 months. He had facial dysmorphism with rotated ears, flat nose and hypertelorism. Neurological examination revealed generalized hypotonia and mental motor retardation. In the immunological screening of the patient, mild lymphopenia, hypogammaglobulinemia and, reduced number of CD3 + T cells 980/mm 3 ) and CD19 + B cells (35 cells/mm 3 ) were detected. He was diagnosed with leaky T -B -NK + SCID. Exome sequence analysis showed the presence of a homozygous pathogenic DCLRE1C variant (c.194C>T; p.T65I [NM_001033855]) and a homozygous pathogenic variant in OBSL1, a gene associated with 3M syndrome (c.3922C>T; p.R1308X [NM_001173431]). Our proband died of sepsis and multiple organ failure. This case illustrates the point that different clinical findings in patients might not be explained with a single genetic defect, and consanguineous marriage increases the coexistence of autosomal recessive diseases. Clinicians should consider whole exome sequencing to identify disease-causing mutations in patients with heterogeneity of clinical findings.